Long-Term Care Healthcare-Associated Infections in 2024: An Analysis of 26,501 Reports - Shawn Kepner; JoAnn Adkins; Rebecca Jones (Patient Safety, 2025)
# Background The Pennsylvania Patient Safety Reporting System (PA-PSRS) is the largest repository of patient safety data of its kind in the United States. The PA-PSRS database contains over 5 million reports, including more than 448,000 long-term care (LTC) healthcare-associated infection (HAI) reports.